A Dietary Supplement Containing Cinnamon, Chromium and Carnosine Decreases Fasting Plasma Glucose and Increases Lean Mass in Overweight or Obese Pre-Diabetic Subjects: A Randomized, Placebo-Controlled Trial - Liu, Yuejun; Cotillard, Aurélie; Vatier, Camille; Bastard, Jean-Philippe; Fellahi, Soraya; Stévant, Marie; Allatif, Omran; Langlois, Clotilde; Bieuvelet, Séverine; Brochot, Amandine; Guilbot, Angèle; Clément, Karine; et al. (PloS one, 2015)
Preventing or slowing the progression of prediabetes to diabetes is a major therapeutic issue. Our aim was to evaluate the effects of 4-month treatment with a dietary supplement containing cinnamon, chromium and carnosine in moderately obese or overweight pre-diabetic subjects, the primary outcome being change in fasting plasma glucose (FPG) level. Other parameters of plasma glucose homeostasis, lipid profile, adiposity and inflammatory markers were also assessed. In a randomized, double-blind, placebo-controlled study, 62 subjects with a FPG level ranging from 5.55 to 7 mmol/L and a body mass index ≥ 25 kg/m(2), unwilling to change their dietary and physical activity habits, were allocated to receive a 4-month treatment with either 1.2 g/day of the dietary supplement or placebo. Patients were followed up until 6 months post-randomization. Four-month treatment with the dietary supplement decreased FPG compared to placebo (-0.24 ± 0.50 vs +0.12 ± 0.59 mmol/L, respectively, p = 0.02), without detectable significant changes in HbA1c. Insulin sensitivity markers, plasma insulin, plasma lipids and inflammatory markers did not differ between the treatment groups. Although there were no significant differences in changes in body weight and energy or macronutrient intakes between the two groups, fat-free mass (%) increased with the dietary supplement compared to placebo (p = 0.02). Subjects with a higher FPG level and a milder inflammatory state at baseline benefited most from the dietary supplement. Four-month treatment with a dietary supplement containing cinnamon, chromium and carnosine decreased FPG and increased fat-free mass in overweight or obese pre-diabetic subjects. These beneficial effects might open up new avenues in the prevention of diabetes. ClinicalTrials.gov NCT01530685.